2021
DOI: 10.1007/s10648-021-09624-7
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Cognitive Load in Digital and Online Learning: a New Perspective on Extraneous Cognitive Load

Abstract: Cognitive load theory has been a major influence for the field of educational psychology. One of the main guidelines of the theory is that extraneous cognitive load should be reduced to leave sufficient cognitive resources for the actual learning to take place. In recent years, research regarding various design factors, in particular from the field of digital and online learning, have challenged this assumption. Interactive learning media, immersion, disfluency, realism, and redundant elements constitute five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 160 publications
(139 citation statements)
references
References 117 publications
8
100
0
1
Order By: Relevance
“…While some studies revealed null results of realism on transfer and comprehension tasks, other studies on processes resulted both in positive and negative effects. An explanation for these contradicting effects may be a mismatch between the cognitive load induced by realism, the cognitive processes it triggers, and the assessment method (Skulmowski & Xu, 2021). While a realistic rendering may help learners in their construction of a mental representation of the surface of objects, it may entail a cognitive cost that reduces learners cognitive capacity for understanding the abstract processes depicted in these visualizations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While some studies revealed null results of realism on transfer and comprehension tasks, other studies on processes resulted both in positive and negative effects. An explanation for these contradicting effects may be a mismatch between the cognitive load induced by realism, the cognitive processes it triggers, and the assessment method (Skulmowski & Xu, 2021). While a realistic rendering may help learners in their construction of a mental representation of the surface of objects, it may entail a cognitive cost that reduces learners cognitive capacity for understanding the abstract processes depicted in these visualizations.…”
Section: Discussionmentioning
confidence: 99%
“…While a realistic rendering may help learners in their construction of a mental representation of the surface of objects, it may entail a cognitive cost that reduces learners cognitive capacity for understanding the abstract processes depicted in these visualizations. If the ensuing test focuses on the process rather than surface details, this cognitive misalignment results in a disadvantage of realistic visualizations (see Skulmowski & Xu, 2021). Therefore, future research that considers the fine-grained aspects of realism and testing methods needs to be conducted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This strategy has recently been adapted to the specific challenges involved in digital learning. The approach of cognitive load alignment posits that cognitive load cannot be avoided in most instances of digital learning (Skulmowski & Xu, 2021 ). For perceptually rich media in particular, this strategy indicates that learning settings must be designed with an appropriate mode of testing in mind.…”
Section: Introductionmentioning
confidence: 99%
“…For perceptually rich media in particular, this strategy indicates that learning settings must be designed with an appropriate mode of testing in mind. Only if a suitable testing method is chosen, the additional cognitive load that may be required by forms of digital learning can be justified (Skulmowski & Xu, 2021 ). For instance, when using realistic visualizations, this approach suggests that the cognitive load caused by realistic details can only be acceptable if the learning objective includes knowledge of such visual details (Skulmowski & Xu, 2021 ).…”
Section: Introductionmentioning
confidence: 99%